Aquabot Water Bottle / Nurul Fatihah Mohd Karim, Nur Irdina Mohd Nasri and Suley Norsyakila Yahya - Mohd Karim, Nurul Fatihah; Mohd Nasri, Nur Irdina; Yahya, Suley Norsyakila (2018)
For this new development product, we had the idea to invent a multifunction water bottle. It looks like the normal water bottle but with the addition of a few compartments and divisions for its own uses respectively. It was designed to be use for showering, cleaning and also drinking. People in this era would prefer something that would ease their everyday life. By inventing this idea of water bottle, these people's need can be fulfilled. This new product would be tested to all ages especially those who love to travels or bagpackers. Getting responses from the survey conducted had put more support to the invention of this new idea. After it has been approved legally, it would be invented and promoted to the markets.